2008
DOI: 10.1111/j.1399-3062.2008.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis after renal transplantation: report of 4 cases in northeastern Brazil

Abstract: Visceral leishmaniasis (VL) is a well recognized opportunistic infection in immunosuppressed patients, which may cause febrile illness. We describe 4 renal transplant patients with VL in an endemic area in Brazil and their response to therapy. In 3 cases the diagnosis was confirmed by bone marrow aspirate that revealed the presence of Leishmania. In 1 case the bone marrow aspirate was inconclusive and the diagnosis was made through spleen biopsy that showed the presence of the parasite. VL needs to be consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 18 publications
1
48
0
1
Order By: Relevance
“…Tal es el caso de los tripanosomas del grupo Salivaria (africanos) (Uzonna et al 1998), (Trypanosoma cruzi (Krettli 1977, Sztein & Kierszenbaum 1993, Bacal et al 2010, Leishmania spp. (Oliveira et al 2008), Toxoplasma gondii (Abedalthagafi et al 2009, García et al 2010, Soléne et al 2010 y Plasmodium falciparum (Grimwade et al 2004). El ejemplo más llamativo causante de este proceso son las infecciones por VIH (Raju et al 2008, Cruz et al 2006, Otieno et al 2006, Jayawardena et al 2008) en las cuales el curso de la enfermedad es más severo producto del debilitamiento del sistema inmune.…”
Section: Resultsunclassified
“…Tal es el caso de los tripanosomas del grupo Salivaria (africanos) (Uzonna et al 1998), (Trypanosoma cruzi (Krettli 1977, Sztein & Kierszenbaum 1993, Bacal et al 2010, Leishmania spp. (Oliveira et al 2008), Toxoplasma gondii (Abedalthagafi et al 2009, García et al 2010, Soléne et al 2010 y Plasmodium falciparum (Grimwade et al 2004). El ejemplo más llamativo causante de este proceso son las infecciones por VIH (Raju et al 2008, Cruz et al 2006, Otieno et al 2006, Jayawardena et al 2008) en las cuales el curso de la enfermedad es más severo producto del debilitamiento del sistema inmune.…”
Section: Resultsunclassified
“…Organ transplants are becoming more widespread in cities that are endemic for visceral leishmaniasis in Brazil, [Broeckaert-van et al 1979; Sirvent-von et al 2004; Oliveira et al 2008] as in Natal and Fortaleza in the Northeast region and Belo Horizonte in the Southeast [Costa 2008; Albuquerque et al 2009; Jeronimo et al 1994]. A brief review of human immune response to Leishmania will help to illustrate why immunocompromised hosts have an increased risk of developing symptomatic VL.…”
Section: Changing Epidemiology Of Visceral Leishmaniasismentioning
confidence: 99%
“…Classically, transmission of Leishmania parasites occurs through sand fly bites, however, studies in France {[7] #248}, Italy {[8] #6}, Spain {[9] #12}, India {[10] #9}, Bangladesh {[11] #250} and Turkey {[12] #251} showed that asymptomatic individuals are found among blood donors, suggesting that transfusion of Leishmania -contaminated blood products might be a source of disease transmission in parallel to syringe sharing {[13] #68} and organ transplantation {[14] #7; [15] #8; [16] #19; [17] #41; [18] #246}. In northeastern Brazil, the prevalence of anti- Leishmania antibodies was 9% among blood donors, increased to 25% in a VL focus and was highest (37%) among poly-transfused hemodialysis patients {[19] #37}.…”
Section: Introductionmentioning
confidence: 99%